Increased Risk for Maternal Anxiety during the COVID-19 Outbreak in Brazil among Pregnant Women without Comorbidities - Nomura, Roseli Mieko Yamamoto; Ubinha, Ana Carla Franco; Tavares, Isabela De Paula; Costa, Maria Laura; Opperman, Maria Lucia Da Rocha; Brock, Marianna Facchinetti; Trapani, Alberto; Damásio, Lia Cruz Vaz Da Costa; Reis, Nadia Stella Viegas; Borges, Vera Therezinha Medeiros [UNESP]; Zaconeta, Alberto Carlos Moreno; Araujo, Ana Cristina Pinheiro Fernandes De; et al. (Federação das Associações de Ginecologia e Obstetrícia, 2021)
Objective To study maternal anxiety in pregnant women without comorbidities in the context of the COVID-19 outbreak in Brazil and to study maternal knowledge and concerns about the pandemic. Methods This is a secondary analysis from a national multicenter cross-sectional study performed in 10 cities, from June to August, 2020, in Brazil. Interviewed postpartum women, without medical or obstetrical comorbidities, were included in the present subanalysis. A structured questionnaire and the Beck Anxiety Inventory (BAI) were applied. Results Out of the 1,662 women, 763 (45.9%) met the criteria for the current analysis and 16.1% presented with moderate and 11.5% with severe maternal anxiety. Moderate or severe maternal anxiety was associated with high school education (odds ratio [OR]:1.58; 95% confidence interval [CI]:1.04-2.40). The protective factor was cohabiting with a partner (OR: 0.46; 95%CI: 0.29-0.73). There was a positive correlation between the total BAI score and receiving information about care in the pandemic (r partial0.15; p < 0.001); concern about vertical transmission of COVID-19 (r partial0.10; p = 0.01); receiving information about breastfeeding (r partial0.08; p = 0.03); concerns about prenatal care (r partial0.10; p = 0.01), and concerns about the baby contracting COVID-19 (r partial0.11; p = 0.004). The correlation was negative in the following aspects: self-confidence in protecting from COVID-19 (r partial0.08; p = 0.04), having learned (r partial0.09; p = 0.01) and self-confidence in breastfeeding (r partial0.22; p < 0.001) in the context of the pandemic. Conclusion The anxiety of pregnant women without medical or obstetrical comorbidities was associated to high school educational level and not living with a partner during the COVID-19 pandemic. Self-confidence in protecting against COVID-19 and knowledge about breastfeeding care during the pandemic reduced maternal anxiety.
Keywords: breastfeeding; childbirth; coronavirus disease 2019; maternal anxiety; pandemic; postpartum; pregnancy; questionnaires